Transformational Leadership, Knowledge Sharing Dan Organizational Commitment Terhadap Job Satisfaction - Sylvyani, Novi Rohma; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The purpose of this study is to analyze knowledge sharing, employee organizational commitment will have a significant impact on employee job satisfaction, this is done to encourage business growth. This study used a structural equation model (SEM) involving 110 respondents, but the data that met the criteria in the study were 122 respondents who worked in Micro, Small and Medium Enterprises (MSMEs) in Indonesia. Analysis of data processing in this study used the Partial Least Square-Structural Equation Modeling (PLS-SEM) system using SmartPLS and assisted with SPSS software. Some of the findings in this study are that Transformational Leadership has a significant positive effect on Knowledge Sharing. Meanwhile, Transformational Leadership has a positive effect on Organizational Commitment. Then Knowledge Sharing has a positive effect on Job Satisfaction. Furthermore, Organizational Commitment has a positive effect on Job Satisfaction. Then Transformational Leadership has a positive effect on Job Satisfaction. Meanwhile, Transformational Leadership has a positive effect on Job Satisfaction which is mediated through Knowledge Sharing. Furthermore, Transformational Leadership has a positive effect on Job Satisfaction which is mediated through Organizational Commitment. Keywords: Transformational Leadership, Knowledge Sharing, Organizational Commitment, and Job Satisfaction